Faktor- Faktor Yang Mempengaruhi Perubahan Laba Kotor pada UMKM Olshop Swarga Bara - Matiin, Nuuridha (Politeknik Raflesia Press, 2024)
Abstrak— The analysis tools used are difference in gross profit, difference in sales, difference in cost of goods sold, difference in selling price, difference in sales quantity, difference in quantity of cost of goods sold, difference in cost of goods sold, difference in quantity of sales and scheme of analysis of gross profit. Keywords — Gross Profit, Sales, Cost of Goods Sold.